Digital Financial Literacy In The Social Media Era: How Financial Influencers And Personal Finance Management Apps Shape Generation Z’s Financial Management Efficiency - Hasyim, Sitti Hajerah; Nurjannah (International Journal of Technology and Education Research, 2026)
The rapid expansion of digital finance, social media-based financial advice, and mobile budgeting technologies has created new opportunities and risks for Generation Z in managing personal finances. Amid global concerns over rising living costs, digital consumerism, financial misinformation, and the increasing influence of financial content creators, digital financial literacy has become essential for young people to make responsible financial decisions. This study examines the effects of financial influencer-based financial education and personal finance management apps on financial management efficiency among Generation Z students. Using an explanatory quantitative approach, data were collected from 34 students of the Faculty of Economics and Business, Universitas Negeri Makassar, selected through purposive sampling. The data were analyzed using multiple linear regression. The findings reveal that financial influencer-based financial education has no significant partial effect on students’ financial management efficiency, indicating that exposure to financial content on social media does not necessarily translate into efficient financial behavior. In contrast, personal finance management apps have a positive and significant effect on financial management efficiency. Simultaneously, both variables significantly affect financial management efficiency. These findings highlight that while financial influencers may increase awareness, practical digital tools play a more direct role in shaping efficient financial behavior among Generation Z.